Foreigner in One’s Own Language: Models of Translating Modern Croatian Dialect Literature into the Standard Croatian Language - Kolar, Mario (Przekłady Literatur Słowiańskich, 2022)
Since there are many differences between the standard Croatian language and the Croatian dialects (Čakavian, Kajkavian and Štokavian), Croatian literary works written in dialects usually include a glossary or otherwise try to bring their language closer to inodialect readers. This paper first reconstructs the models of translating modern Croatian dialect literature into the standard Croatian language and then analyses the advantages and disadvantages of each model.